2022
DOI: 10.3389/fmed.2022.859521
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 27 Novel Variants in Genes COL4A3, COL4A4, and COL4A5 in Lithuanian Families With Alport Syndrome

Abstract: Introduction:Alport syndrome (AS) is an inherited disorder characterized by hematuria, proteinuria, and kidney function impairment, and frequently associated with extrarenal manifestations. Pathogenic variants in COL4A5 usually cause X-linked Alport syndrome (XLAS), whereas those in the COL4A3 or COL4A4 genes are associated with autosomal dominant (AD) or recessive (AR) inheritance. To date, more than 3000 different disease-causing variants in COL4A5, COL4A3, and COL4A4 have been identified. The aim of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…As of now, over 3,000 pathogenic variants of the COL4A3, COL4A4 and COL4A5 genes have been reported [10]. The general consensus in literature is that numerous mutations of aforementioned genes are still to be described and have their phenotype and clinical significance determined to ensure adequate introduction of treatment and assessment of prognosis [11]. The exact prevalence of pathogenic variants is unknown, however a recent population-based study using the data from the gnomAD cohort has shown a frequency of 1/2320 individuals with an incidence of a predicted pathogenic mutation in the COL4A5 gene, while 1/106 individuals had a heterozygous predicted pathogenic mutation in the COL4A3 or COL4A4 genes, and 1/88,866 subjects that had two heterozygous predicted pathogenic mutations [12].…”
Section: Discussionmentioning
confidence: 99%
“…As of now, over 3,000 pathogenic variants of the COL4A3, COL4A4 and COL4A5 genes have been reported [10]. The general consensus in literature is that numerous mutations of aforementioned genes are still to be described and have their phenotype and clinical significance determined to ensure adequate introduction of treatment and assessment of prognosis [11]. The exact prevalence of pathogenic variants is unknown, however a recent population-based study using the data from the gnomAD cohort has shown a frequency of 1/2320 individuals with an incidence of a predicted pathogenic mutation in the COL4A5 gene, while 1/106 individuals had a heterozygous predicted pathogenic mutation in the COL4A3 or COL4A4 genes, and 1/88,866 subjects that had two heterozygous predicted pathogenic mutations [12].…”
Section: Discussionmentioning
confidence: 99%
“…Since each gene is located on different chromosomes (COL4A3 with COL4A3 on chromosome 2 and COL4A5 on the X chromosome), the inheritance of the disease also occurs differently [Momota et al, 1998;Zhao et al, 2019;Zhao et al, 2020]. To the best of our knowledge, more than 3,000 pathogenic variants have been reported in COL4A5, COL4A3, and COL4A4 to date [Cerkauskaite et al, 2022]. The most common genetic cause of AS is variants in the COL4A5 gene on the Xq22.3, which encodes for type IV collagen alpha-5 chain.…”
Section: Introductionmentioning
confidence: 99%